Letter of reply - Bennett, G; Newman, P; Polydor, A (Oxford Institute for Energy Studies, 2015)
In response to the surprisingly emotional article, ‘New EU rules may be a fix for something that isn’t broken’, we would argue that it is not only regulators who are looking for a verifiable solution to benchmarking, but actually the market more generally.